Psychological barriers in the acquisition of second language : a non-native perspective - Ahmed, Md. Kawser (Penerbit Universiti Kebangsaan Malaysia, 2019)
Acquisition of second language (L2) learners especially non-native learners face several affective barriers. Affective barriers popularly known as psychological barriers pose a great obstacle potentially in the acquisition of second language. Anxiety, lack of confidence and limitation of adjustment to the changed environment make second language learners unnerving and ambivalent. Non-native learners feel shaky, overlapping and ambiguous in the perception and the production of second language. Likewise, teachers’ disinterest to promote learners rather positively enhances the scope of psychological crisis. Practically, learners do have a potential weakness on linguistic knowledge like four skills of English language and understanding the needs of students. The focus of this paper will be upon the identification of valid factors which in human psychology create obstruction to achieve mastery over language. In addition, realistic presentation of non-native learning context, affective conflict and constraints of motivation often lead to maximizing psychological barriers. In fact this paper will specifically deal with cross cultural viewpoints-native or non-native with analytic discussion.